Pengaruh Gaya Kepemimpinan, Budaya Organisasi, dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Motivasi pada PDAM Tirta Mayang Kota Jambi - Muhammad Emil; Albetris Albetris (J-MAS (Jurnal Manajemen dan Sains), 2019)
In every organization both government and private, human is an important asset in an effort to achieve the goals that have been determined. Leadership style, organizational culture, work motivation and performance of employees who reside within the organization need to be organized in order to achieve organizational goals. Style leadership, organizational culture and work environment and motivation is one of several factors that can affect employee performance. This study aims to test and analyze these variables on employee performance PDAM Tirta Mayang City Jambi. The study was conducted by using path analysis using SPSS version 22.0 in analyzed data. The test results showed that the hypothesis of leadership style, organizational culture and motivation have positive and significant influence on performance, and testing work environment hypothesis have negative and insignificant effect on employee performance of PDAM Tirta Mayang Jambi City.